Significant harm as a criminal unlawfulness sign of illegal actions in relation to private life information and personal data - Zakhilko, Kiryl S. (Journal of the Belarusian State University. Law, 2022)
The concept of significant harm as a criminal unlawfulness sign of illegal actions in relation to private life information and personal data (art. 2031 of the Criminal Code of the Republic of Belarus) is considered. The content of the sign and methods for determining of significant harm as a criminal unlawfulness sign of illegal actions in relation to private life information and personal data are determined. The causal relationship between illegal actions in relation to private life information and personal data and their consequences is analysed.